PEMBELAJARAN SIKAP KEAKRABAN DALAM MENGATASI PERILAKU BULLYING DI MADRASAH IBTIDAIYAH NEGERI KOTA BIMA - Trimansyah, Trimansyah (FASHLUNA, 2023)
Bullying behavior that occurs can be overcome by instilling an attitude of mutual acceptance, respect and establishing friendly relationships. This attitude is the most important attitude to be practiced in today's life, to create a peaceful life among others and a peaceful environment, both in the Madrasah environment as an educational platform for generations and in the social environment in general, it is necessary to instill the value of togetherness from an early age to establish friendly relationships, if This relationship can be cultivated well, then good developments in the future will follow and it will be easy to develop. Friendly learning carried out by MIN Bima City to overcome bullying behavior through several methods, namely as follows: (a) Learning that instills understanding, namely teaching students about the benefits and importance of a friendly attitude and the negative impacts of bullying behavior. (b) learning by example, that is, apart from instilling understanding and knowledge, it is very necessary to follow this by providing good examples and role models to students. (c) learning and teaching to instill the habit of establishing close relationships so that it becomes a habit that is ingrained in students to avoid bullying behavior. (d) real action learning, namely after teaching knowledge and understanding and giving examples, it is necessary to pay attention that good attitudes must be implemented in everyday life. (e) learning to give advice as a driver of children's awareness to understand the nature and benefits of friendly attitudes and the bad behavior of bullying that must be avoided. (f) learning that provides sanctions to strengthen students' attitudes towards the meaning of kindness. (g) civilizing learning, that is, after being taught a good attitude, it will be applied repeatedly with istioqomah.